Overview of Cattle and Small Ruminants Breeding in Bayburt Province - Kani Yavuz (Turkish Journal of Agriculture: Food Science and Technology)
Crop and animal production constitute a large part of the people's livelihoods in Bayburt province. In addition, the province has become one of the important animal husbandry centers of the region due to the fact that it is a transit point between the Eastern Anatolia region and the Black Sea region. But the number of small farms in Bayburt province is still very large, and the number of farms that are members of grower organizations is quite small. In addition, the migration of the young population from villages leads to an increase in the average age of the population engaged in animal husbandry and a decrease in the number of animals that can be raised depending on the labor force. In this review, the general status of cattle and small ruminants livestock in Bayburt province was given and the level of livestock in Bayburt province was revealed with current data.